Hubungan Tingkat Stres Akademik dengan Prokrastinasi Belajar Mahasiswa di Kabupaten Kudus - Resti Dwiana Marsella; Karina Vebrina Islamica; Fareel Aby Firnandi; Sahrul Amin Muhanif; Fina Fakhriyah; Erik Aditiya Ismaya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aimed to examine the relationship between academic stress and learning procrastination among university students in Kudus Regency. A quantitative correlational research design was employed. The study involved 40 students selected through accidental sampling. Data were collected using a Likert-scale questionnaire consisting of 32 items, including 16 items measuring academic stress and 16 items measuring learning procrastination. Data were analyzed using descriptive statistics, reliability testing, the Shapiro–Wilk normality test, and Spearman rank correlation analysis with the assistance of IBM SPSS Statistics. The reliability test yielded a Cronbach’s Alpha value of 0.848, indicating excellent internal consistency of the instrument. The correlation analysis showed a correlation coefficient of rₛ = 0.292 with a significance value of 0.068 (p > 0.05), indicating a positive but weak and statistically insignificant relationship between academic stress and learning procrastination. These findings suggest that academic stress is not the primary factor influencing learning procrastination among university students. Other factors, such as self-regulation, time management, learning motivation, self-efficacy, and the ability to manage distractions, are likely to contribute to procrastination behavior. Therefore, efforts to reduce learning procrastination should emphasize the development of self-regulation and effective learning skills in addition to managing academic stress.